Effect of temperature on the protonation of N-(2-hydroxyethyl)ethylenediamine-N, N′, N′-triacetic acid in aqueous solutions: Potentiometric and calorimetric studies. (June 2015) - Li, Xingliang; Zhang, Zhicheng; Endrizzi, Francesco; Martin, Leigh R.; Luo, Shunzhong; Rao, Linfeng
Abstract : Graphical abstract: The first two steps of protonation of HEDTA occur on the diamine nitrogen atoms and are exothermic, while the third step occurs on the oxygen of one carboxylate group and is slightly endothermic. This trend is in good agreement with the enthalpies of protonation directly determined by calorimetry. The energetics of the protonation can be well explained by the difference in the degree of hydration between the amine nitrogen and carboxylate oxygen sites. Highlights: The effect of temperature on the protonation of HEDTA was evaluated by thermodynamic measurements. The first two protonation steps are exothermic while the third step is endothermic. Calorimetry and NMR data indicate that the first two protonation steps occur on the amine nitrogen atoms. Abstract: The TALSPEAK process (Trivalent Actinide Lanthanide Separations by Phosphorus-reagent Extraction from Aqueous Komplexes) has been demonstrated in several pilot-scale operations to be effective at separating trivalent actinides (An 3+ ) from trivalent lanthanides (Ln 3+ ). However, fundamental studies have revealed undesired aspects of TALSPEAK, such as the significant partitioning of Na +, lactic acid, and water into the organic phase, thermodynamically unpredictable pH dependence, and the slow extraction kinetics. In the modified TALSPEAK process, the combination of the aqueous holdback complexant HEDTA ( N -(2-hydroxyethyl)ethylenediamine- N, N ′, N ′-triacetic acid) with the extractant HEH[EHP] (2-ethyl(hexyl) phosphonic acid mono-2-ethylhexyl ester) in the organic phase has been found to exhibit a nearly flat pH dependence between 2.5 and 4.5 and more rapid phase transfer kinetics for the heavier lanthanides. To help understand the speciation of Ln 3+ and An 3+ in the modified TALSPEAK, systematic studies are underway on the thermodynamics of major reactions in the HEDTA system under conditions relevant to the process ( e.g., higher temperatures). Thermodynamics of the protonation and complexation of HEDTA with Ln 3+ were studied at variable temperatures. Equilibrium constants and enthalpies were determined by a combination of techniques including potentiometry and calorimetry. This paper presents the protonation constants of HEDTA at T  = (25 to 70) °C. The potentiometric titrations have demonstrated that, stepwise, the first two protonation constants decrease and the third one slightly increases with the increase of temperature. This trend is in good agreement with the enthalpy of protonation directly determined by calorimetry. The results of NMR analysis further confirm that the first two protonation reactions occur on the diamine nitrogen atoms, while the third protonation reaction occurs on the oxygen of a carboxylate group. These data, in conjunction with the thermodynamic parameters of Ln 3+ /An 3+ complexes with HEDTA at different temperatures, will help to predict the speciation and temperature-dependent behavior of Ln 3+ /An 3+ in the modified TALSPEAK process.